Solving the MASUM sport league scheduling problem using hybrid genetic algorithm and constraint-based reasoning [compact disc] (Skudai : Universiti Teknologi Malaysia, 2006)
Thesis (Sarjana Sains (Sains Komputer)) - Universiti Teknologi Malaysia, 2006